CREATION OF THE MULTILEVEL EDUCATION SYSTEM IN THE FIELD OF QUALITY AS A FACTOR OF SUSTAINABLE DEVELOPMENT - Vladimir V. Okrepilov (Высшее образование в России)
An international experience shows that the sustainable development of the society notably depends on the quality of the human factor which is characterized by the lifetime, gross domestic product, and education level. This defines the status and significance of education in the field of quality. The article highlights the issues concerning the organization of the system of multilevel continuing education in the field of economics of quality within the U.N.O. conception "Education for Sustainable Development". Such kind of education is treated as an essential factor to achieve the balanced and well-off functioning of all social spheres. The paper discusses some results of the experience in creation of such system in St.-Petersburg.